2021
DOI: 10.1042/bsr20202726
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting association of Leptin receptor polymorphisms and haplotypes with polycystic ovary syndrome in Bahraini and Tunisian women: a case–control study

Abstract: Background. This study examined the contribution of ethnicity to the association of leptin receptor gene (LEPR) genetic variants with polycystic ovary syndrome (PCOS) in Tunisian and Bahraini Arabic-speaking women. Methods. Subjects consisted of 320 women with PCOS, and 446 eumenorrhic women from Tunisia, and 242 women with PCOS and 238 controls from Bahrain. Genotyping of (exonic) rs1137100 and rs1137101 and (intronic) rs2025804 LEPR variants was done by allelic exclusion. Results. The minor allele frequencie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…This discrepancy may be due to the difference in the studied population. Although the association of rs7799039 and rs1137101 polymorphisms with some metabolic disorders including obesity, insulin resistance and dyslipidemia has been evaluated [ 25 28 ], few studies have been carried out on the association between these polymorphisms and PCOS [ 29 , 30 ]. The present study indicates for the first time the association of rs7799039 and rs1137101 polymorphisms with PCOS-related infertility in Iranian women.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This discrepancy may be due to the difference in the studied population. Although the association of rs7799039 and rs1137101 polymorphisms with some metabolic disorders including obesity, insulin resistance and dyslipidemia has been evaluated [ 25 28 ], few studies have been carried out on the association between these polymorphisms and PCOS [ 29 , 30 ]. The present study indicates for the first time the association of rs7799039 and rs1137101 polymorphisms with PCOS-related infertility in Iranian women.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study showed that rs1137101 polymorphism of the LEPR gene is associated with PCOS and PCOS-related infertility. There are conflicting data about the association between this polymorphism and PCOS in the different populations [ 29 , 59 ]. Li et.al showed that the G allele of rs1137101polymorphism is significantly associated with the decreased risk of PCOS in the Korean population [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations